2019
DOI: 10.4149/bll_2019_132
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intralipid administration on calcium therapy in verapamil toxicity

Abstract: Aim: Lipid emulsions are promising with regard to the treatment of toxicity by agents of high lipophilic nature. Our objective is to investigate the effi cacy of intralipid 20% and calcium administration at different times when symptoms of cardiac toxicity occur during verapamil infusion. Method: 24 adult male Spraque-Dawley rats were randomly divided into 4 different groups, the control group, calcium group, calcium following 20% intralipid group and concomitant 20% intralipid and calcium group. Following mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…A previous study used 15 mg kg -1 calcium chloride (equivalent to approximately 5.45 mg kg -1 calcium) in a lipid emulsion treatment for verapamil toxicity (3). Thus, the calcium dosage used in this study is approximately 55-folds lower than that in the previous study (1,3). Second, it is unclear what type of solution (intralipid or normal saline) was used to dissolve calcium (0.2 mmol kg -1 ) in the group administered with loading dose intralipid followed by calcium (Group L-Ca) (1).…”
Section: Dear Editormentioning
confidence: 91%
See 1 more Smart Citation
“…A previous study used 15 mg kg -1 calcium chloride (equivalent to approximately 5.45 mg kg -1 calcium) in a lipid emulsion treatment for verapamil toxicity (3). Thus, the calcium dosage used in this study is approximately 55-folds lower than that in the previous study (1,3). Second, it is unclear what type of solution (intralipid or normal saline) was used to dissolve calcium (0.2 mmol kg -1 ) in the group administered with loading dose intralipid followed by calcium (Group L-Ca) (1).…”
Section: Dear Editormentioning
confidence: 91%
“…We have read the interesting report titled "Effect of intralipid administration on calcium therapy in verapamil toxicity," recently published in Bratislava Medical Journal (1). Lipid emulsions can effectively attenuate severe vasodilation induced by toxic doses of the highly lipid soluble calcium channel blocker, verapamil (2).…”
Section: Dear Editormentioning
confidence: 99%
“…[8][9] A large evidence revealed that intravenous lipid has positive effect on the treatment of some medical problems such as verapamil toxicity, malathion-induced hepatotoxicity and chronic intestinal failure. [10][11] In the literature, there are few solid data about using intravenous lipid as a feasible, safe, cost-effective agent in the treatment of RIF patients. [12][13] In this study, it was aimed to investigate the effect of intravenous lipid on outcomes measured in terms of implantation rate and pregnancy rate in patients with unexplained RIF undergoing IVF/ICSI.…”
Section: Introductionmentioning
confidence: 99%